2021
DOI: 10.1080/03323315.2021.1964568
|View full text |Cite
|
Sign up to set email alerts
|

The DEIS programme as a policy aimed at combating educational disadvantage: fit for purpose?

Abstract: Existing research in the area of educational disadvantage in the Irish context is located either within the historiography of policy in the area or in contemporary macro analysis of dominant trends. The existing canon of research tells us that prolonged periods of unemployment and poorer health outcomes are features of early school leavers, that the educational experience of young people are reflected in their future life trajectories, and that inter-generational transmission is common. While broader macro ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Having said that, the majority of Catholic secondary schools in Ireland, like their Protestant counterparts, continue to function to enable groups with various levels of privilege to succeed academically and, in doing so, perpetuate existing inequalities. The greatest challenge the education system and wider society now face is the fact that despite a number of measures introduced over decades to democratise education, participation in education in Ireland continues to be shaped by social class, reproducing intergenerational advantages for dominant social groups (Harford, Hyland, and Fleming, 2022;Fleming and Harford, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Having said that, the majority of Catholic secondary schools in Ireland, like their Protestant counterparts, continue to function to enable groups with various levels of privilege to succeed academically and, in doing so, perpetuate existing inequalities. The greatest challenge the education system and wider society now face is the fact that despite a number of measures introduced over decades to democratise education, participation in education in Ireland continues to be shaped by social class, reproducing intergenerational advantages for dominant social groups (Harford, Hyland, and Fleming, 2022;Fleming and Harford, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, the lack of a control group in DEIS evaluations limits the conclusions that can be drawn and it has been noted that the multifaceted nature of the program makes it difficult to disentangle which aspects may work best (Smyth et al, 2015). Some have argued that resources provided to DEIS schools are inadequate (Fleming & Harford, 2021). However, the European Commission (2019, p. 15) suggests that initiatives, including DEIS, "have made Irish secondary schools positive forces for inclusion".…”
Section: Identifying and Addressing Educational Disadvantage In Irelandmentioning
confidence: 99%
“…While one-third of St. Greg's student population was made up of White settled Irish students from disadvantaged backgrounds, one third comprised (non-Traveller) minority ethnic students, and one third Traveller students, an unusually high number. While high levels of diversity are not unusual in DEIS schools [82,83], some DEIS schools are more diverse than others.…”
Section: School Socio-demographics Reputation and Academic Expectationsmentioning
confidence: 99%
“…Research has suggested that a school with a diverse student population may be viewed in a negative light by teachers, parents, and students, if the diverse students are also from socio-economically disadvantaged backgrounds [84,85]. While none of the student participants from the different participant groups attributed the school's negative reputation to their own socio-economic or ethnic group, they were acutely aware that their school was positioned within a "demonised school" discourse ( [86]; see also [82]). Hollingworth and Archer [81] found that demonised school discourses are often resisted and contested by young people, and in this study, some of the student participants resisted the stigmatised view of their school.…”
Section: School Socio-demographics Reputation and Academic Expectationsmentioning
confidence: 99%
See 1 more Smart Citation